Evaluation of oxidative stress, the activities of paraoxonase and arylesterase in patients with subclinic hypothyroidism - Cebeci, E.; Oner, F.A.; Usta, et al., M. (Acta Biomedica Atenei Parmensis, 2012)
Introduction: In subclinical hypothyroidism (SH), serum lipid and lipoprotein concentrations are frequently changed. Compared to the normal population, the levels of oxidized low-density lipoprotein (LDL) cholesterol are higher and the levels of high density lipoprotein (HDL) cholesterol are lower. In SH patients, the mechanism of atherosclerosis may be attributed to the lipid abnormalities. There is evidence showing that, oxidation plays an important role during the process of atherosclerosis, preventing the lipid peroxidation of paraoxonase 1 and thereby, acting against the atherosclerosis. In this study, we evaluated the activity of paraoxonase and arylesterase in subclinical hypothyroidism and investigated its relation with oxidative stress. Method: The study enrolled 25 cases with SH and 20 healthy controls. The patient group and the control group were compared in terms of the activity of paraoxonase and arylesterase and the oxidative stress index. Results: Between two groups, no significant difference was found in terms of age, gender, total cholesterol, low-molecular weighted lipoprotein, high-molecular weighted lipoprotein. In SH group, the activity of paraoxonase was significantly lower than that observed in the control group (p=0.01). Also, the activity of arylesterase was significantly lower in the group with subclinical hypothyroidism (p=0.03). Oxidative stress index was found to be significantly higher in the group with subclinical hypothyroidism compared to the healthy controls (p<0.01). Oxidative stress index showed a strong positive correlation with the levels of TSH in all cases (r=0.60, p<0.01. Conclusion: Consequently, in SH, the activity of paraoxonase and arylesterase were significantly low and oxidative stress was significantly high. Lower activities of paraoxonase and arylesterase indicated increased oxidative damage in SH. This may be useful to elucidate the mechanism of atherosclerosis in SH. In addition, these findings suggested that the activities of paraoxonase and arylesterase may be used for the determination of therapeutical response and during the follow-up.